(untitled) (CIPEEX, 2022)
THE USE OF ANABOLIC ANDROGENIC STEROIDS (AAS) HAS SEVERAL LINES OF INDICATIONS AND MOTIVATIONS FOR USE AS A THERAPEUTIC, AESTHETIC AND SPORTS CONDUCT. IN THE SEARCH FOR GREAT RESULTS IN SHORT PERIODS OF TIME, MANY PEOPLE LOOK FOR AAS, PROVIDING A GREAT DISORDER EMPHASIZED BY EXACERBATED CONSUMPTION THAT RESULTS IN HARM BEYOND WHAT IS EXPECTED IN THE SHORT AND ESPECIALLY LONG TERM. THIS ARTICLE IS AN INTEGRATIVE LITERATURE REVIEW WITH THE OBJECTIVE OF DESCRIBING THE EFFECTS OF THE USE OF ANABOLIC ANDROGENIC STEROIDS BY YOUNG ADULTS AND THE LONG-TERM CONSEQUENCES. THE SEARCH WAS CARRIED OUT IN THE NATIONAL LIBRARY OF MEDICINE AND NATIONAL INSTITUTES OF HEALTH (PUBMED), VIRTUAL HEALTH LIBRARY (BVS) AND SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO). EIGHTEEN STUDIES WERE SELECTED, WITH THE INDICATION OF INCLUSION THE HARMS OF LONG-TERM AAS USE IN THE YOUNG ADULT POPULATION, AVAILABLE IN FULL, IN ENGLISH AND PORTUGUESE, FROM THE LAST SIX YEARS (2017-2022). AND EXCLUDED ARTICLES THAT DO NOT ANSWER THE GUIDING QUESTION. IT WAS CONCLUDED THAT THE MAIN EFFECTS CAUSED BY THE USE OF THESE SUBSTANCES ARE: HYPERTENSION, HEART AND KIDNEY FAILURE, HEPATOTOXICITY, REDUCTION IN THE DENSITY OF BASAL NEURONS AND IN THE HIPPOCAMPUS, HIGHER LEVELS OF ANGER AND AGGRESSION, VOICE ALTERATION AND HYPERTROPHY OF THE CLITORIS. GUIDING QUESTION. IT WAS CONCLUDED THAT THE MAIN EFFECTS CAUSED BY THE USE OF THESE SUBSTANCES ARE: HYPERTENSION, HEART AND KIDNEY FAILURE, HEPATOTOXICITY, REDUCTION IN THE DENSITY OF BASAL NEURONS AND IN THE HIPPOCAMPUS, HIGHER LEVELS OF ANGER AND AGGRESSION, VOICE ALTERATION AND HYPERTROPHY OF THE CLITORIS.